Comparative analysis of the characteristics of insulating vegetable liquids for high voltage electrical equipment - Абрамов, Володимир Борисович; Проценко, Олександр Ростиславович (Technology audit and production reserves, 2016)
This is a summary of investigations of influence of raw vegetable materials on the characteristics of liquids which can be used as an insulator in high voltage electrical equipment. Raw materials influence not only the initial characteristics of produced liquids, but also on changes in these parameters while they’re being used. In presenting the results of research attention is given to achieving the desired characteristics of the thermo-oxidative stability of such liquids, the differences of the aging process in which paper insulation, possibilities of diagnostics of defects on the basis of gasification equipment control. It is noted that the use of different vegetable raw materials leads to differences in the manufacturing process and use of these liquids. Among the positive effects of the use of insulating vegetable liquids in high-voltage electrical equipment, one can note an increase in durability of cellulose insulation in them. However, usage of such equipment will require development and application of techniques for its control which differ from those which are conventionally used for mineral oils.